KEARIFAN BUDAYA LOKAL MADURA SEBAGAI MEDIA PERSUASIF (Analisis Semiotika Komunikasi Roland Barthes dalam Iklan Samsung Galaxy Versi Gading dan Giselle di Pulau Madura) - Sri Wahyuningsih (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article aims to provide an overview of the cultural wisdom of Madura in advertisement Samsung Galaxy Ivory version by Indonesian celebritis Gading and Giselle in the island of Madura. This study, usin a semiotic analysis of Roland Barthes, tried to unlock the meaning of the signs that are used and re veal the hidden message contained in this advertisement. The author conducted a qualitative study with a research focus on scenes depicting local wisdom of Madurese culture, and then select scenes in advertising that represents local cultural wisdom Madura. Local knowledge of Madurese culture has its own persuasive power. Theme choice by producer of the advertisement is very interesting and has its own character, especially of cattle races, clothing style Madurese, as well as their language and dialect. Madura Island in East Java island region known as the island of salt, and exotic, so well known nationally and internationally. The results of the analysis of mobile phone mentioned found some connotations as follows: (1) the existence of a form of Madurese community thanksgiving in the lens, and (2) cow races, clothing Madura, and language of madurese is indigenous culture of Madura.